Curricular Overhaul in Goiás: a participatory process - Reginato Ribeiro, Maria José (2007)
This report describes the curricular overhaul for the second segment of Primary School, developed by the Goiás State Secretary of Education, from 2004 to 2006. The new project was constructed using a participatory process, which involved professionals from the school system and establishment of partnerships with the Center for Studies and Research in Education, Culture and Community Action (Centro de Estudos e Pesquisas em Educação, Cultura e Ação Comunitária – CENPEC) and local universities. This process was consolidated in a movement articulating the schools, under secretaries and the Office of the Secretary, providing for training meetings of multidisciplinary teams with teachers, coordinators and principals. The course taken by this overhaul was recorded and published in four editions, called "Debate on Curriculum" ("Currículo em Debate").